EFFECT OF BUTTERFLY HUG METHOD ON REDUCING ANXIETY LEVELS IN DORMITORY STUDENTS IN FACING THE RISK OF COVID-19 TRANSMISSION AT SMP MTA GEMOLONG - Dwi Ariani Sulistyowati; Lu’lu’ Azhari (Bajang Institute, 2025)
Covid-19 is a disease with a high transmission rate. This makes boarding students vulnerable to experiencing anxiety in facing the challenges of the high spread of Covid-19 in dormitories because activities are carried out 24 hours face-to-face. Anxiety that is not addressed immediately will negatively impact dormitories students, so appropriate education and intervention are needed. This study aims to determine the effect of the butterfly hug method on reducing anxiety levels in dormitory students in facing the risk of covid-19 transmission at SMP MTA Gemolong. This study used quasi experimental design. The sampling technique used purposive sampling technique and obtained a number of 76 participants who were divided into experimental group (n = 38) and kontrol group (n = 38). The instrument used was the Hamilton Anxiety Rating Scale (HARS). Data analysis used Wilcoxon Test and Mann Whitney Test with p value < 0.05. Data analysis using the Wilcoxon Test in the experimental group showed p value = 0,000 and in the kontrol group showed p value = 0,141. Hypothesis testing using the Mann Whitney Test in both groups obtained p value = 0,026. There is an effect of the butterfly hug method on reducing anxiety levels in dormitory students facing the risk of covid-19 transmission at SMP MTA Gemolong.